Colposcopy combined with dynamic spectral imaging. A prospective clinical study. (January 2016) - Coronado, Pluvio J.; Fasero, María
Abstract: Objective: To analyze the value of dynamic spectral imaging (DSI) compared to, and as an adjunct to, conventional colposcopy (CC) in the diagnosis of cervical intraepithelial neoplasia (CIN). Study design: Four hundred seventy-nine women referred for colposcopy after an abnormal Pap-smear (≥ASC-US) to the Low Genital Tract Unit of the San Carlos Clinical Hospital in Madrid, Spain during the years 2012–2014 were examined simultaneously by CC and DSI. Thirty-six cases (8.1%) were excluded because the DSI map was not calculated. The gold standard for comparisons was the final histological diagnosis performed by punch biopsy or LEEP. Results: Out of the 443 cases, 293 were found to be negative for CIN, 109 had CIN1 and 41 were found with CIN2+. The sensitivity of CC to detect those with CIN2+ lesions was 73.2% and the specificity 92.3%. Using the DSI map as an adjunct, led to a statistically significant increase of the sensitivity to 87.8% with a concomitant drop in specificity to 85.6%. The adjunctive use of DSI increased the sensitivity for CIN2+ also in the high-risk group of the 65 cases with an identified HPV16/18 infection; CC had a sensitivity of 88.9%, which increased to 100%. The specificity dropped from 91.1% to 87.5%. Conclusions: Combining conventional colposcopy with DSI mapping improves the capability to detect cervical lesions.